PEMBUATAN BIOETANOL DARI LIMBAH KAYU SENGON (Falcataria moluccana (Miq.) Barneby & J.W. Grimes) DENGAN METODE SUBSTRAT KONSENTRASI TINGGI - Ina; T. Beuna Bardant (BRIN Publishing, 2017)
Various sawmilling industries of high, medium and small enterprises operate in Indonesia. During log conversion into sawn timber, wood waste occurs in the form of left over cut and sawdust. Small cut waste is lignocellulose material which is potentially used for bioethanol production. This paper studies the possibility of bioethanol production from sengon sawmill waste. High loading substrate method was applied by hydrolyzing high concentration substrate, i.e 15, 25 and 35% and two concentrations of enzymes (12.5 and 15 FPU/g substrate). Result showed that the treatment of 25% substrate concentration and 15 FPU/g cellulase substrate produced the highest reducing sugar of 248.3 mg/mL, while the substrate concentration of 35% generated the highest ethanol content i.e 17.7% and recovery about 38.4%. It can be concluded that the high loading substrate method could increase the ethanol concentration made from sengon wood waste.